PENGARUH WAKTU PAPARAN RADIASI UV-C TERHADAP KARAKTERISTIK RAPAT ARUS DIFUSI ION PADA MEMBRAN KITOSAN - Ika Paramitha Putri, Putu; Sumadiyasa, Made; Rupiasih, Ni Nyoman (BULETIN FISIKA; Vol 17 No 1 (2016): BULETIN FISIKA, 2016)
It has conducted research about the effects of UV-C irradiation to the current density of ion diffusion characteristics of chitosan membranes. A series of chitosan membranes with various ratios of components was used such as 1%, 2%, 3% and4%, the electrolyte solution was NaCl with various concentration of 0.1 mM , 1 mM, 10 mM, 100 mM, and 1000 mM, and time exposure of 5, 15, 30, and 60 minutes. Ion transport processes were carried out in a cell membrane model which composed of two compartments, and the potential difference was measured using a pair of Activon AEP calomel electrodes. All the measurements were conducted at room temperature of about 28.1 o C. The result showed that the current density increased with increasing some parameters e.g. the ratio of concentration of solution in both compartments (C1/C2), the amount of chitosan (1%, 2%, 3% and4%), and exposure time.